ANALYSIS OF DIFFERENT FORMS OF SHOTS IN FOOTBALL - Miroslav Radoman; Miroslav Smajić; Aleksandar Joksimović; Bogdan Tomić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The area of technical-tactical activities is very interesting and unexplored, especially because the game from year to year changes faster. The aim of this research is to perform analysis of different forms of shots in football (in the official statistics) and their association with outcomes of football matches at the World Cup 2006. in Germany (FIFA World Cup Germany 2006.). The sample consists of observations of 64 games played at the World Cup 2006. in Germany. Sample characteristics are elements of games that are leading the official statistics, which is promoted for all FIFA competitions that take place under its auspices, including the World Championships. Of five elements for analysis was selected four. Based on the analysis set forth can be concluded that the team winning the game stands out significantly in all analyzed characteristics in relation to the game the team with a score draw or a defeat where the difference is less. All teams that have achieved the victory had offensive tactics or were technically dominant in relation to the opponent.